“My tongue, my own thing”: Reading Sanaaq - Henitiuk, Valerie (TTR, 2016)
Mitiarjuk, who has been called the “accidental Inuit novelist” (Martin, 2014), began writing Sanaaq in the mid-1950s and was “discovered” in the late 1960s by a doctoral student of Claude Lévi-Strauss. Bernard Saladin d’Anglure took up this text as his anthropology thesis topic, guided its completion, arranged for its 1984 publication in Inuktitut syllabics, and in 2002 published a French translation; his own former student, Peter Frost, has recently (2013) translated the French version into English. Without the training and tools that would equip an outsider to appreciate Inuit writing and the oral traditions from which it arises, and to judge it on its own merits, scholarly assessment by other than specialist anthropologists or ethnographers has often been felt to be beyond the reach of southerners. Nonetheless, a younger generation of literary scholars such as Keavy Martin, inspired by the work of J. Edward Chamberlin, Robert Allen Warrior and Craig Womack, are working to redress such attitudes. Bringing to bear for the first time the perspective of translation studies, this paper will suggest some ways we can move from ethnography’s purported aim of a systematic study of people and cultures to a rigorous and ethical study of these translated texts, reading them explicitly asliterature, as well as (and perhaps more importantly) asliterary translations.